The Role of Play in the Social Development of Grey Seal (Halichoerus grypus) Pups with Comparative Notes on the Harbour Seal (Phoca vitulina) - Susan C. Wilson (Animals, 2024)
Juvenile grey seals are known to be highly social, interacting with contact behaviours interpreted as gentle play. However, minimal sociality of pups with their mothers and among weaned pups has been suggested. The present study aimed to observe the natural social interactions of pups to track the early ontogeny of their sociality. Pup behaviour at a salt marsh colony on the east coast of England was video-recorded. Pups interacted with their mothers around suckling bouts and after weaning as they gathered around pools. The records were transcribed to spreadsheets in 30 s time segments to estimate the frequency and co-occurrence of different behaviours. Mother-pup interaction comprised nosing contacts and sometimes contact play, involving one laying the head and fore-flipper over the other. Initial weaned pup encounters involved tentative nosing and defensive splashing, indicating contact shyness. However, socially orientated locomotor play, supine posturing, and exaggerated raising of fore- and hind-flippers led to reduced shyness and pups following one another towards the sea. Archive data on subadult interactions and on harbour seal behaviours were re-analysed. Gentle play-like contact between mother–pup, juvenile, and adult pairs is interpreted here as a universal mode of social bonding, underscoring the social structure of both grey and harbour seals.